A single-blind, dose escalation, phase I study of high-fluence light-emitting diode-red light (LED-RL) on human skin: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Ho, Derek; Kraeva, Ekaterina; Wun, Ted; Isseroff, R.; Jagdeo, Jared
Abstract Background Skin fibrosis is involved in a variety of pathologic conditions ranging from scar formation secondary to surgery or trauma to immune-mediated processes. Skin fibrosis is a significant international health problem with an estimated incidence of greater than 100 million people affected per year worldwide with few effective treatment options available. Preliminary in vitro data generated by our research group suggests that red light can function as a stand-alone treatment for skin fibrosis. To our knowledge, no prior clinical trials have been performed to determine the safety of high-fluence (dose) light-emitting diode-red light (LED-RL) phototherapy. The goal of this study is to evaluate the safety of LED-RL fluences from 160 J/cm2 up to 640 J/cm2 in healthy subjects. Methods/design This is a single-blind, dose escalation, randomized controlled, phase I study to evaluate the safety of high-fluence LED-RL on human skin. The protocol for dose escalation requires subjects be enrolled sequentially in groups of five. Within each group, three subjects will be randomized to LED-RL phototherapy and two subjects randomized to mock therapy. Subjects in group 1 randomized to LED-RL phototherapy will receive the maximum recommended starting dose (160 J/cm2 ). LED-RL dose will be escalated in subsequent groups (320 J/cm2, 480 J/cm2 and 640 J/cm2 ). The maximally tolerated dose (MTD) is defined as the dose level below the dose producing unacceptable but reversible toxicity and is considered to be the upper limit of subject tolerance. After either a MTD has been established, or the study endpoint of 640 J/cm2 has been achieved, an additional 27 LED-RL phototherapy subjects (for a total of 30) and 18 mock therapy subjects (for a total of 20) (determined randomly) will be enrolled. Each subject will receive a total of nine procedures, three times per week for three consecutive weeks. Discussion This study may provide important safety information on the effects of high-fluence LED-RL phototherapy on human skin and help facilitate future phase II studies to evaluate the efficacy of high-fluence LED-RL as a potential noninvasive, safe, portable, at-home therapy for treatment of skin fibrosis. Trial registration ClinicalTrials.govNCT02630303 . Registered on 9 December 2015.